Getting Human Papillomavirus Vaccination Back on Track: A National Survey - Kahn, Benjamin Z.; Huang, Qian; Thompson, Peyton; Gilkey, Melissa B.; Alton Dailey, Susan; Brewer, Noel T. (Journal of adolescent health, 2023)
Adolescent human papillomavirus (HPV) vaccine uptake in the United States dropped during the COVID-19 pandemic due to a decrease in well visits. This study sought to identify opportunities for primary care professionals (PCPs) to get adolescent vaccination back on track. In early 2021, we recruited 1,047 PCPs (71% physicians) who provided adolescent vaccines in the United States from an existing panel. Participants completed an online survey about changes in adolescent HPV vaccine uptake and actions taken to promote vaccination during the pandemic, as well as intentions to engage in activities to increase adolescent vaccination in the next 3 months. A substantial proportion of PCPs (43%) reported that HPV vaccine uptake decreased in the first year of the pandemic; few (7%) PCPs reported an increase in uptake. PCPs reporting increased uptake were more likely to have used nurse-only vaccination visits, held drop-in and drive-through vaccination clinics, and used telehealth visits to recommend vaccination (all p < .05). Nearly two-thirds (62%) of all PCPs planned to promote adolescent vaccine uptake in the next 3 months. Planning was more common among PCPs who believed HPV vaccine uptake at their clinics increased during the pandemic, who saw more than 10 adolescent patients per week, who had ever reviewed their clinic's vaccination rates, and were nurses (all p < .05). Many PCPs saw HPV vaccination drop during the pandemic. Several interventions could help clinics get HPV vaccination back on track, including increasing the availability of nurse-only vaccination visits and vaccination-only clinics.